Pengembangan Instrumen Four Tier Multiple Test Materi Pewarisan Sifat Berbasis Kearifan Lokal Banten untuk Mengukur Tingkat Pemahaman Konsep Siswa Kelas IX - Fajrin Nur Azizah; Liska Berlian; Nofita Fajariyanti (UNIB Press, 2026)
The test instrument currently used by teachers is only a single-level multiple-choice test. The use of a single-level multiple-choice test instrument is still less able to indicate students' conceptual understanding because it is easy to answer by guessing. The Four Tier Multiple Test instrument has a format that is equipped with the level of confidence of answers and reasons, challenging students to be confident in choosing answers. This study aims to describe the level of validity of the Four Tier Multiple Test instrument and to describe the level of student response to the Four Tier Multiple Test instrument. The research method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation & Evaluation) development model. The data collection instruments used in this study were validation questionnaires and student response questionnaires. This study involved 85 ninth-grade students as respondents to describe the level of student response to the Four Tier Multiple Test instrument. The level of validity of the Four Tier Multiple Test instrument as assessed by material expert validators was 94.38% (very valid), media expert validators 97.05% (very valid), evaluation expert validators 91.05% (very valid) and science teacher validators 88.99% (very valid). The level of student response to the Four Tier Multiple Test instrument was 84.83%, in the very good category.